Effects of recombinant IL‐17F intranasal inoculation against Streptococcus pneumoniae infection in a murine model. (15th December 2014) - Chen, Ling; Guo, Sheng; Wu, Liangxia; Hao, Chunli; Xu, Wanting; Zhang, Jianhua
Abstract Interleukin‐17F (IL‐17F) is an important member of IL‐17 cytokine family, which plays important roles in host defense against microbial infections. Streptococcus pneumoniae is a common pathogen associated with several invasive and noninvasive pneumococcal diseases, and mucosal immune response plays crucial roles in defenses against pneumococcal infection. Thus, intranasal inoculation may be an alternative approach against pneumococci. In this study, BALB/c mice were intranasally inoculated with recombinant IL‐17F (rIL‐17F) prior to S. pneumoniae (American Type Culture Collection 6303, serotype 3) infection. As compared with the control group, numbers of total leukocyte, neutrophil, and macrophage in lungs were significantly increased in mice inoculated with rIL‐17F. The levels of macrophage inflammatory protein 1α (MIP‐1α), MIP‐2β, and interferon γ were significantly increased in bronchoalveolar lavage fluid and culture supernatant of splenocytes from mice inoculated with rIL‐17F. rIL‐17F inoculation also significantly elevated β‐defensin‐2 expression in lung tissues. Furthermore, compared with S. pneumoniae infection group, rIL‐17F inoculation prior to infection significantly reduced S. pneumoniae colonization in lungs. These findings demonstrated that rIL‐17F intranasal inoculation strengthened host defense against pneumococci, which may be developed to prevent pneumococcal infection.